The influence of phosphorus precursor on the structure and properties of SiO2–P2O5–CaO bioactive glass. (19th July 2017) - Ren, Huihui; Tian, Yun; Li, Ailing; Martin, Richard A; Qiu, Dong
Abstract: Bioactive glasses (BGs) are one of the most promising bone regeneration materials because they can bond to bone and simulate new bone growth. Sol–gel methods for producing BG are well established, however challenges still remain in selecting and optimizing the precursors. Even for BGs with the same final composition, different precursors may lead to different structures and properties of the gel derived BG. In this work, three different phosphorus precursors, phytic acid (PA), triethyl phosphate (TEP) and n-butyl phosphate (BP) were used to prepare BG (54.2%SiO2 –35%CaO–10.8%P2 O5, mol%). The obtained materials were characterized by TGA, FTIR, XRD, HEXRD, solid state 31 P, 29 Si NMR and by in vitro tests in SBF. It was found that the materials prepared by TEP or BP showed small amounts of crystallization, whereas the resulting material prepared by PA remained amorphous and had more P atoms as orthophosphate. In vitro assays indicated that all these materials were bioactive, while the BG prepared by PA showed the highest in vitro bioactivity, followed by TEP and, finally, BP. Based on these observations, it appears that phosphorus precursors have a significant impact on both the structure and bioactivity of the sol–gel derived BG. Results suggest that PA should be used in preference to TEP or n-butyl phosphate for the synthesis of sol gels. PA may improve the homogeneity of the sol gel glasses, reduce crystallization and lower stabilization temperatures.